Factors associated with good health among older persons who received a preventive home visit: a cross-sectional study - Anna Nivestam; Albert Westergren; Pia Petersson; Maria Haak (BMC, 2020)
Abstract Background The ageing population is increasing worldwide, and this trend is bringing challenges both for the older person and for society. In order to meet the challenges a comprehensive approach is needed involving both health promotion and risk prevention. The preventive home visit is a public health intervention used around the world with the purpose of promoting health and preventing risk among older persons. However, most preventive home visits are focused on questions asking about risks. In order to strengthen the health promotion perspective during the preventive home visits, factors associated with good health need to be identified. The aim of this study was therefore to determine which factors were associated with good self-rated health among older persons who received preventive home visit. Methods This was a register study with a cross-sectional design, including older persons (≥75 years old), living in their own homes, and that had received preventive home visit. Data were collected during a period of 9 months, in two municipalities in the south of Sweden. A questionnaire covered mental, physical and lifestyle factors were used at home visit. Binary logistic regression was used to analyse the data. Results In total, 619 older persons were included in the study; 55.4% were women, and the mean age was 80.6 years (standard deviation 2.2 years). The following items were significantly associated with good health (after adjustment for age and gender): being able to do things that make one feel valuable, having no physical problems affecting participation in social activities, not feeling sad, not having reduced energy, and not having impaired endurance. Conclusions The main conclusion of this study is that questions focusing on risks could be seen from a health promotion perspective and could thus be turned into assets with a positive impact on older persons' health. Furthermore, the mental and physical factors identified in the results as associated with good health have implications for the person's ability to feel valuable and participate in social activities. The results suggest that issues regarding both health promotion as well as risk prevention must be brought up during the preventive home visit.